User Experience (UX) Analysis on the Rifzki ID Mobile Website Using the System Usability Scale (SUS) Method - Rifzki Adiyaksa; Aji Primajaya; Dadang Yusup (International Journal of Education, Information Technology, and Others, 2023)
A personal website is a form of self-marketing or self-branding so that it is considered very important to do, in the current ease of technology all these things It is quite possible to be done by everyone easily and very quickly. Only by understanding a little programming language can one create a personal website, but this is not only related to creating but also related to attracting interest people to visit the website page or not, a website must be well built and planned quite carefully, using the Rifzki ID website usability scale (SUS) system method analyzed to find out the user experience when visiting the site or page on the website so that the results of the analysis can later become material for improvement to Rifzki ID website user interface in the future